Epidemic curves and the profile of patients hospitalized by COVID-19 in a border region - Merielly Kunkel; Érica Alves Ferreira Gordillo; Laiz Mangini Cicchelero; Franz Porzsolt; Mara Cristina Ripoli Meira; Helder Ferreira; Neide Martins Moreira; Larissa Djanilda Parra da Luz; Nathalia Halax Orfão; Reinaldo Antonio Silva-Sobrinho (Universidade de São Paulo, 2024)
Objective: to describe the epidemic curves and analyze the epidemiological profile of patients hospitalized with COVID-19 in a triple border city. Method: descriptive-quantitative. The population consisted of COVID-19 cases that required hospitalization, analyzing variables such as: age, gender, race/color, city where they lived, occupation, pregnant woman, institutionalized patient and evolution. Descriptive statistical analysis and analysis of variance and chi-square tests were used. Results: four epidemic curves were identified in the studied period. Among hospitalized cases, males predominated (55%). Cure was the most frequent outcome in curves 1, 2 and 4, but with no statistical difference (p = 0.2916). Curve 3 showed a higher frequency of deaths (41.70%) in relation to cures (38.77%). The mean ages were significantly different between the curves, with curve 4 having the lowest mean age. Conclusion: it was concluded that the epidemic curves were influenced by different situations; unvaccinated population, easing of restrictive measures, reopening of the Brazil-Paraguay border, interruption of control actions, crowding of people and circulation of new variants of the disease. Through the epidemiological profile of hospitalized patients, it was concluded that being male, of mixed race/color, aged between 61 and 85 years, and being deprived of freedom were associated with hospitalization and the occurrence of death.